2013
DOI: 10.1007/978-3-642-39405-8_30
|View full text |Cite
|
Sign up to set email alerts
|

Toward Task-Based Mental Models of Human-Robot Teaming: A Bayesian Approach

Abstract: Abstract. We consider a set of team-based information tasks, meaning that the team's goals are to choose behaviors that provide or enhance information available to the team. These information tasks occur across a region of space and must be performed for a period of time. We present a Bayesian model for (a) how information flows in the world and (b) how information is altered in the world by the location and perceptions of both humans and robots. Building from this model, we specify the requirements for a robo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…and they help people to describe, explain and predict events in their environment." Other work (Goodrich & Yi, 2013;Kiesler & Goetz, 2002;Nikolaidis & Shah, 2013) has shown the effect of shared mental models on team performance for human-robot teams, as well. Using these insights, we propose a way for the robot to communicate its internal state to the human.…”
Section: Communication Of Robot Internal Statementioning
confidence: 98%
“…and they help people to describe, explain and predict events in their environment." Other work (Goodrich & Yi, 2013;Kiesler & Goetz, 2002;Nikolaidis & Shah, 2013) has shown the effect of shared mental models on team performance for human-robot teams, as well. Using these insights, we propose a way for the robot to communicate its internal state to the human.…”
Section: Communication Of Robot Internal Statementioning
confidence: 98%
“…In this case, an autonomous team member is considered to be capable of working alongside human team member(s) by interacting with other team members (Schooley et al, 1993;Krogmann, 1999;Endsley, 2015), making its own decision about its actions during the task, and carrying out taskwork and teamwork (McNeese et al, 2018). In team literature, it is clear that autonomous agents have grown more common in different contexts, e.g., software (Ball et al, 2010) and robotics (Cox, 2013;Goodrich and Yi, 2013;Chen and Barnes, 2014; Bartlett and Cooke, 2015;Zhang et al, 2015;Demir et al, 2018c). However, considering an autonomous agent as a teammate is challenging (Klein et al, 2004) and requires effective teamwork functions (McNeese et al, 2018): understanding its own task, being aware of others' tasks (Salas et al, 2005), and effective interaction (namely communication and coordination) with other teammates (Gorman et al, 2010;Cooke et al, 2013).…”
Section: Teaming With Autonomous Agentsmentioning
confidence: 99%
“…As SMMs have been implicated in successful human teamwork, it is theorized that they can facilitate interaction and coordination in mixed human-agent teams as well. Several studies have shown promising results in software systems [12,18] and more recently in robots [19][20][21]. However, these studies often focused on a single aspect of the SMM (e.g., predicting workload [22]) and were not grounded in a comprehensive formal or computational framework.…”
Section: Shared Mental Modelsmentioning
confidence: 99%